Analysis of the Implementation of Mental Health Screening of Pregnant Women by Midwives in Bantul Regency, Yogyakarta: A Mixed Methods Study - Rohani, Rohani; Pratiwi, Cesa Septiana; Sarwinanti, Sarwinanti (Journal of Health and Nutrition Research, 2025)
Mental health disorders during pregnancy are a very important issue for maternal and fetal health. Screening for conditions such as depression and anxiety is needed, but often overlooked in Indonesia. This study aims to analyze the implementation of mental health screening of pregnant women by midwives in Bantul Regency, Yogyakarta. This study used a mixed methods approach   with a sequential explanatory approach consisting of a quantitative online survey followed by qualitative FGDs. The results of the study showed that 115 midwives 67.0% only screened less than 25% of the total pregnant women they served. Only a small proportion conducted routine screening (13.0% 5-10 times, and 14.8% more than 10 times). Qualitative findings from 12 midwives confirmed that while screening can identify mental health concerns, its application is inconsistent and faces substantial barriers, including limited time, privacy, insufficient training, and lack of screening tools. Despite these challenges, midwives showed a generally positive perception of the importance of mental health screening for both mothers and fetuses. Supporting factors for screening include policy, education, integrated services, professional collaboration, SOPs, and additional human resources. In conclusion, this study highlights gaps in mental health screening practices and emphasizes the importance of improving training, access to screening tools, and supportive policies. Further research is needed to explore strategies for addressing these barriers and consider the role of technology, while multicenter studies could be conducted to expand the scope of this study, making the results more representative